1997
DOI: 10.3189/s0022143000035024
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and fall-out of137Cs and other radionuclides over Antarctica

Abstract: ABSTRACT. Thi s a rticle a ims to give a comp rehensive vi ew of the distributi on patte rns [or na tura l and artifical r a di onucl ides ove r Antarctica. \Ve foc us this stud y on 137 Cs, 210Pb and tritium . Appl ying vario us statistica l m ethods, we show th at the depositio n or rad ionuclid es revea ls a struc tured di stributi o n, although loca l d r ift red istributi on a nd the snow-s urface roughness disturb th e representati ve ness o f sa mpl es and produce a "noise" effec t. The depos iti on o f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…137 Cs, 90 Sr, and 240 Pu deposition in fresh snow is related to the atmospheric thermonuclear tests that occurred between 1955 and 1980. Two main 137 Cs, 90 Sr, and 240 Pu peaks at 1955 and 1965 have been well identified in Antarctic snow (Feely et al, ; Koide et al, , ; Pourchet et al, , ). These peaks are used as time markers because 137 Cs, 90 Sr, and 240 Pu are immobile tracers associated to the particulate phase in snow.…”
Section: Resultsmentioning
confidence: 92%
“…137 Cs, 90 Sr, and 240 Pu deposition in fresh snow is related to the atmospheric thermonuclear tests that occurred between 1955 and 1980. Two main 137 Cs, 90 Sr, and 240 Pu peaks at 1955 and 1965 have been well identified in Antarctic snow (Feely et al, ; Koide et al, , ; Pourchet et al, , ). These peaks are used as time markers because 137 Cs, 90 Sr, and 240 Pu are immobile tracers associated to the particulate phase in snow.…”
Section: Resultsmentioning
confidence: 92%
“…Nevertheless, very distinct radioactive peaks in continuous tritium profiles are also observed [ Jouzel et al , 1979; Oerter et al , 1999; Stenni et al , 2002; Frezzotti et al , 2005]. The timing of radioactive deposition from the nuclear tests is well known in Antarctica [ Wilgain et al , 1965; Feely et al , 1966; Jouzel et al , 1979; Oerter et al , 1999; Pourchet et al , 1983, 1997, 2003; Magand et al , 2004], with the maximum radioactivity peaks in 1954–1955 and 1965–1966 used as convenient horizons for dating snow and ice layers and measuring SMB. Jouzel et al [1979] observed the largest tritium peak at the South Pole during 1966.…”
Section: Measurement Techniquesmentioning
confidence: 99%
“…The atmosphere is the major source of 210 Pb deposited on the Antarctic ice sheet. Many factors contribute to the low radon (and its daughter nuclide) concentrations in Antarctica [ Pourchet et al , 1997, 2003]. These include ice that prevents the escape of radon from the Antarctic geological basement, the surrounding ocean without radon emission, and the time required for air masses to move from continental areas (the main source of radon emission) to the south polar region.…”
Section: Measurement Techniquesmentioning
confidence: 99%
“…Accurate dating in snow by 210 Pb is possible under the following assumptions: (1) the mean 210 Pb activity in precipitation has remained constant over the time period covered by the samples, (2) the 226 Ra concentrations within the firn/ice samples are negligible, (3) no diffusion of air into the ice sheet occurs (bearing additional 222 Rn), and (4) 210 Pb remains at its initial place of deposition (no vertical transportation by water from melting snow). Evaluation of SMB over the past few decades by this method usually lead to these values being judged reliable in melt‐free areas [ Pourchet et al , 1997, 2003], even if none of the previous assumptions was perfectly fulfilled.…”
Section: Review and Quality Rating Of Smb Measurement Techniquesmentioning
confidence: 99%
“…SMB data sources treated in this work, are mainly issued from Vaughan et al 's [1999] data set (V99), in which most of the references containing SMB data across Antarctica, from 1950s to 1997, has been compiled. Some SMB data from Lorius et al [1968], Pourchet et al [1983, 1997], Lipenkov et al [1998], Stenni et al [2000], and Pourchet et al [2003] along the Dumont–d'Urville–Dome Concordia (Ddu‐DC) and Mirny‐Vostok (MNY‐VK) routes which were not included in V99 data set are added. We finally improve and complete this compilation by addition of new observed SMB data produced by the Italian and French ITASE activities [ Frezzotti et al , 2004; Magand et al , 2004; Frezzotti et al , 2005], the Russian Antarctic Expeditions (RAE) with intensive pit studying program from 1998 to 2000, in the vicinity of Vostok station [ Ekaykin et al , 2002, 2005] and the Australian National Antarctic Research Expeditions (ANARE) [ Smith et al , 2002; Goodwin et al , 2003] in our study sector since 1998.…”
Section: Introductionmentioning
confidence: 99%